2004
DOI: 10.1111/j.1745-4573.2004.tb00717.x
|View full text |Cite
|
Sign up to set email alerts
|

EFFECT OF ULTIMATE pH ON THE QUALITY CHARACTERISTICS OF PORK

Abstract: A study was conducted to characterize the relationship between Longissimus thoracis ultimate pH (LTpH) and pork quality. Animals (n =47) were selected based on LTpH measured at 24 h postmortem. Data were analyzed using regression procedures with ultimate pH as the independent variable, and relationships were determined to be linear (L), quadratic (Ql or cubic (C). Ultimate pH explained 79% (C) of the variation in subjective color, which increased as pH increased. Drip loss, purge loss and L* value decreased as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
33
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(40 citation statements)
references
References 25 publications
5
33
0
2
Order By: Relevance
“…This was in agreement with Stier et al (2001) found who that the muscle pH decline triggered by preslaughter conditions influences meat colour (Stier et al, 2001). Previous study has shown that 70% of the variation in L*, b* values and 28% of the a* value in LD was explained by ultimate pH (Bidner et al, 2004).Other study also report that 43% of the variation in L* value was explained by the ultimate pH (Brewer et al, 2001). The association between higher muscle pH and higher colour might be explained by the facts that muscle pH could impact endogenous oxygen-consuming enzymes which influences the relative ratio of the myoglobin species Mb and MbO 2 as well as the internal reflectance of the meat (Lindahl et al, 2001).…”
Section: Meat Quality Measurementmentioning
confidence: 97%
“…This was in agreement with Stier et al (2001) found who that the muscle pH decline triggered by preslaughter conditions influences meat colour (Stier et al, 2001). Previous study has shown that 70% of the variation in L*, b* values and 28% of the a* value in LD was explained by ultimate pH (Bidner et al, 2004).Other study also report that 43% of the variation in L* value was explained by the ultimate pH (Brewer et al, 2001). The association between higher muscle pH and higher colour might be explained by the facts that muscle pH could impact endogenous oxygen-consuming enzymes which influences the relative ratio of the myoglobin species Mb and MbO 2 as well as the internal reflectance of the meat (Lindahl et al, 2001).…”
Section: Meat Quality Measurementmentioning
confidence: 97%
“…Indeed, increased proteolysis is associated with paler colour and a condition known as pale soft exudative (Wilhelm et al, 2010). However, drip loss was not decreased in Treatment M possibly due to the higher pH at 24 h pm (Bidner et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…In fermented meat products the decrease of pH is also due to the action of LAB, making the meat proteins coagulate and generating texture (Ravyts et al 2012). Other studies (Huff-Lonergan et al 2002;Bryhni et al 2003;Bidner et al 2004) have shown, that higher ultimate pH tended to be associated with juicier meat and the lowest juiciness was observed at approximately 5.4 (Bidner et al 2004). Since 1940 lactobaccilli and pediococci are used as acidifiers, usually in combination with Gram-positive, catalase positive cocci (Ravyts et al 2012).…”
Section: Resultsmentioning
confidence: 99%